Final cuts : new tales of Hollywood horror and other spectacles - Datlow, Ellen (Blumhouse Books/Anchor Books, 2020)
From the secret reels of a notoriously cursed cinematic masterpiece to the debauched livestreams of modern movie junkies who will do anything for clicks, Final Cuts brings together new and terrifying stories inspired by the many screens we can't peel our eyes away from. Inspired by the rich golden age of the film and television industries as well as the new media present, this new anthology reveals what evils hide behind the scenes and between the frames of our favorite medium. With original stories from a diverse list of some of the best-known names in horror, Final Cuts will haunt you long after the credits roll.